A comparative analysis of the performances of macroeconomic indicators during the Global Financial Crisis, COVID-19 Pandemic, and the Russia-Ukraine War: The Ghanaian case - Bright Tetteh; Enoch Ntsiful (Research in Globalization, 2023)
The recent downturn of the Ghanaian economy has been numerously attributed by the government and policymakers to past global shocks. By using a descriptive approach, this study aimed to examine the performances of macroeconomic indicators of the Ghanaian economy during the three most recent and impactful global shocks - the Global Financial Crisis (GFC), the COVID-19 pandemic, and the Russia-Ukraine war. Through comparative analysis, the study shows under which shock an indicator was trending downwards, upwards, or stable - on average. The study found that relative to the other shocks, cocoa and gold prices increased most under the GFC, and therefore, their exports were also averagely more favourable under the GFC, but timber exports and oil and gas imports were trending downwards. Exports of timber and timber products and imports of oil and gas increased under the COVID-19 shock but gold export and trade balance declined, on average, during the COVID-19 shock. Exchange rate, oil and gas prices, and food and non-food inflation were found to have been unprecedently high during the Russian-Ukraine war compared with all other shocks, and this reflects the worst record of economic growth during the Russian-Ukraine war compared with all other shocks. Appropriate recommendations are made for policymakers to enhance domestic food and non-food production to curb inflation and add value to commodity exports to improve economic growth and trade balance.
Keywords: 330; COVID-19 Pandemic; Ghana; Global financial crisis; Macroeconomic performance; Russia-Ukraine war